2021
DOI: 10.28991/cej-2021-03091725
|View full text |Cite
|
Sign up to set email alerts
|

Strengths of Struts and Nodal Zones for Strut-and-Tie Model Design of Reinforced Concrete Corbels

Abstract: The strut-and-tie model (STM) method is useful for the limit state design of reinforced concrete (RC) corbels. However, for the rational design of RC corbels, designers must accurately determine the strengths of concrete struts and nodal zones to check the strength conditions of a selected STM and the anchorage of reinforcing bars in nodal zones. In this study, the authors suggested a numerical process for determining the strengths of concrete struts and nodal zones in RC corbel STMs. The technique incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Corbels made with bidirectionally distributed reinforcement were also found to perform more favorably in terms of crack control. Yun and Lee 18 conducted a numerical investigation to evaluate the strength of struts and nodal zones in corbels with high accuracy. Shakir and Abdlsaheb 19 investigated methods to strengthen the RC corbels and reported that using near‐surface‐mounted bars and applying carbon fiber reinforced polymer sheets could effectively increase the capacity of corbels.…”
Section: Introductionmentioning
confidence: 99%
“…Corbels made with bidirectionally distributed reinforcement were also found to perform more favorably in terms of crack control. Yun and Lee 18 conducted a numerical investigation to evaluate the strength of struts and nodal zones in corbels with high accuracy. Shakir and Abdlsaheb 19 investigated methods to strengthen the RC corbels and reported that using near‐surface‐mounted bars and applying carbon fiber reinforced polymer sheets could effectively increase the capacity of corbels.…”
Section: Introductionmentioning
confidence: 99%
“…The vertical stirrups were efficient in increasing the corbel′s ductility but made little contribution to the bearing capacity. Yun and Lee [10] proposed a corbel′s bearing capacity formula, including the shear span-depth ratio, aspect ratio, concrete strength, and reinforcement area. Hamoodi′s [11] test results showed that the corbel's bearing capacity improved by 20.2% when the shear span-depth ratio decreased from 0.50 to 0.35.…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, there is still a lack of research into the accuracy and rationality of the TTM, particularly for the corbels with the same designed bearing capacity but configured with different concrete compressive strength or shear spans. Previous research used the variable-controlling method to investigate the effects of factors on the bearing capacity of corbels [9][10][11][12][13], for which the designed bearing capacities were not the same. In actual corbel design, the design load is determined first.…”
Section: Introductionmentioning
confidence: 99%